REKONSTRUKSI HUBUNGAN NEGARA DAN WARGA NEGARA DALAM HISTORISASI KONSTITUSI THAILAND - Shalihah, Aini; Lukman Hakim; Sujudi, Muhammad (Universitas Teknologi Surabaya, 2025)
Thailand is a country with a majority Buddhist population. Buddhist life has colored almost all aspects of life in Thailand, both in government (kingdom), system, education curriculum, law and so on. However, there are also several other religions practiced by some Thai people including Islam, Christianity, Hinduism, Confucianism and Singh. In percentage, the Muslim population in the Land of the White Elephant is only around 5.5% of the total citizens who are predominantly Buddhist. Looking at the percentage, almost all Malay Muslims live in Pattani Province. This quantitative fact has marginalized them socially and politically and made them a minority ethnic group in Thailand. The purpose of this writing is to analyze the reconstruction of the relationship between the state and citizens in the historicization of the Thai constitution. The method used is the normative legal method using a legislative approach and a conceptual approach. The results of the study show that during modern history, Thailand has continued to strengthen democratic institutions to ensure that the voices of all people are heard and respected. In recent years, grassroots community groups and independent organizations have appeared to play a more active role. This has led Thailand to a participatory democracy that encourages all levels of society to be more actively involved in shaping the national agenda. Thai democracy continues to experience ups and downs. A number of political crises have occurred, triggered by differences in views and ideologies among groups in Thai society in guarding the integrity of the nation in the 21st century. Keywords: Historicization, Thai Constitution, Reconstruction, State & Citizen Relations